Overview of innovation research in tourist companies in the function of development - Koldžin Dragica; Medić Vera (University Educons, Faculty of Sports and Tourism, Novi Sad, 2019)
Due to the impressive growth of the tourism industry, tourism is recognised as a key driver of socio-economic progress. Globalisation and changes in the environment, privatisation and restructuring of enterprises greatly influence the success of the tourism industry. This dynamic growth is accompanied by extremely strong competition that creates high pressure on tourist companies to innovate constantly in order to survive and grow. A limited number of studies relating to innovation in tourism represent a significant problem. As limited available research indicates, one of the basic internal barriers to innovation in tourism enterprises is their size. These are mostly small companies with great personal turnover. A particular problem is that innovations in this field are of intangible nature and consist of behavioural changes. This leads to scarce opportunities for their protection, which is an especially underresearched field. Identification of barriers to innovation in tourism companies and work on their elimination represent the first steps in the direction of further research required for an even more intensive impact of this economic sector on the economic growth of the country.